The Associations Between Pre- and Postnatal Maternal Symptoms of Distress and Preschooler's Symptoms of ADHD, Oppositional Defiant Disorder, Conduct Disorder, and Anxiety. Issue 7 (May 2020) - Bendiksen, Bothild; Aase, Heidi; Diep, Lien My; Svensson, Elisabeth; Friis, Svein; Zeiner, Pål
Objective: The objective of this article is to examine the associations between pre- and postnatal maternal distress and preschooler's symptoms of ADHD, Oppositional Defiant Disorder (ODD), Conduct Disorder (CD), and anxiety, by timing and gender.Method: Children, aged 3.5 years ( N = 1, 195), recruited from the Norwegian Mother and Child Cohort Study, were assessed with a semistructured parental psychiatric interview. Perinatal maternal symptoms of distress were assessed by Symptom Checklist (SCL-5); Poisson regression was used to examine the associations.Results: Mid-gestational maternal distress significantly increased the average number of child symptoms, ranging between 3.8% for ADHD hyperactive–impulsive (ADHD-HI) and 8.7% for anxiety. The combination of high maternal scores of distress both pre- and postnatally were associated with increased risk of child symptoms of anxiety (relative risk [RR] = 2.10; 95% confidence interval [CI] = [1.43, 3.07]), CD (RR = 1.83; 95% CI = [1.33, 2.51]), and ODD (RR = 1.30; 95% CI = [1.03, 1.64]), with minor sex differences.Conclusion: Maternal distress during mid-gestation was associated with ADHD, behavioral, and emotional symptoms in preschool children. Continued exposure into the postnatal period may further increase these risk associations .